Spontaneous Retroperitoneal Bleeding in a Patient with Systemic Lupus Erythematosus - Wei-Hung Chen; Deng-Ho Yang (Medicina, 2023)
Background and Objectives: Systemic lupus erythematosus (SLE) is a disease with multiple organ involvement, and spontaneous hemorrhage, especially perirenal hemorrhage, is rare. Case Presentation: We report the case of a 19-year-old teenager with SLE who experienced left flank pain and hypovolemic shock. Abdominal computed tomography revealed a large left retroperitoneal hematoma. Recurrent hypovolemic shock occurred despite the transcatheter arterial embolization of the left renal artery. Repetitive abdominal computed tomography results showed active hemorrhage. Result: An exploratory laparotomy was used to confirm descending colonic mesenteric artery bleeding, which was resolved. The patient needed temporary regular kidney replacement therapy for active lupus nephritis, which terminated one month after discharge. Conclusions: When patients with SLE experience acute abdominal pain, flank pain, or back pain combined with hypovolemia, there is a higher risk of bleeding due to spontaneous hemorrhage, which should be included in the differential diagnosis. Therefore, early diagnosis and adequate emergency intervention are necessary.